Effective Throughput of Cognitive Multiple Access Channel Under Collision Constraints and Imperfect Sensing - Zhengying Xiao; Xianzhong Xie; Senlin Zhang (Dianxin kexue)
The problem of effective throughput of multiple secondary users access to the spectrum of primary user in the cognitive multiple access channel under collision constraints and imperfect channel state information was discussed. Effective throughput was defined and used as the performance metric for secondary users under opportunity spectrum access（OSA）. The channel quality information was considered and limited number of channel samples were used to estimate the parameter of unknown channel quality distribution and the performance of secondary users under imperfect sensing was analyzed. The performance of secondary users under perfect sensing and imperfect sensing was compared by simulations. Moreover, the validity of proposed access strategy was verified by comparing it with other algorithm.